Structure and function of CD31 - Newton, J (1997)
The regulated interaction of leukocyte with endothelium is of key importance during normal immune surveillance and leukocyte infiltration to sites of infection in the inflammatory response. This thesis is concerned with the structure and function of CD31 (platelet-endothelial cell adhesion molecule-1), one of the adhesion molecules implicated in these processes. Previous work has shown both in vivo and in vitro that CD31 is involved in the final step of leukocyte recruitment, transmigration across the endothelial monolayer. CD31 mediated adhesion is complex, since it is capable of mediating multiple adhesive interactions, both to itself (homophilic adhesion) and to other ligands (heterophilic adhesion). In order to study homophilic adhesion, an heterologous cell-protein assay was used in combination with recombinant chimeric CD31Fc fusion proteins, ICAM-3/CD31 chimeras and chimeras between human and murine CD31. These reagents located the homophilic binding site to the NH2-terminal domains 1 and 2, but also define a non-binding accessory role for the membrane proximal domains. Using site-directed mutagenesis to target all of the exposed charged residues in domain 1 and a subset of charged residues in domain 2, five residues were identified, mutations in which resulted in inhibition of homophilic adhesion. These residues map to both faces of the domain 1 immunoglobulinlike fold, suggesting that each molecule of CD31 interacts with two others. A novel zipper model of homophilic adhesion involving CD31 lateral association analogous to that seen amongst cadherins is proposed on the basis of these results. Evidence for lateral association of CD31 to form dimers was obtained from biophysical, biochemical and molecular biology techniques. These show that Cd31 exists in an equilibrium between monomeric and dimeric forms both in solution as soluble recombinant protein, and at the cell surface. In solution the affinity of the interaction was calculated to lie in the range 12-14μM. A large panel of anti-CD31 monoclonal antibodies were generated and tested for their ability to effect homophilic adhesion. Inhibitory antibodies were identified, mapping throughout the extracellular domain, away from the ligand binding site. In addition possible stimulating antibodies mapping to the membrane proximal domains were also identified. This indicates that CDS 1 may be induced to undergo conformational changes which effect homophilic adhesion, and it is proposed that these conformational changes may be linked to the ability of CD31 to form laterally associated dimers. Using the reagents described above, a screen of haematopoietic cell lines identified a novel heterophilic interaction, which was shown to be mediated by the integrin ανβ3. Proteinprotein assays were used to confirm a direct physical association between CD31 and ανβ3, and to map the integrin binding site to the third immunoglobulin-like fold of CD31. The functional significance of this interaction was assessed in neutrophil transmigration assays, in which both anti-CD31 and anti-ανβ3 antibodies were found to partially inhibit neutrophil transmigration.